Measurement of Calcium, Inorganic Phosphate and Albumin Levels in Serum of Iraqi Hypertensive Male Patients - Amal R. Farhan; Eham A. Ali; Shatha M.J. Al-khateeb (Journal of Madenat Alelem University College, 2012)
Hypertension is a major health problem in adults, and contributes to cardiovascular disease. Malnutrition or deficiency in different nutrients found to be a risk factor for pathogenesis of essential hypertension. No clear association of calcium with blood pressure level could be identified. In this work serum calcium and albumin in hypertensive patients were compared with healthy control. Thirty uncomplicated, untreated, hypertensive, but otherwise have no other systemic diseases males, ranging in age from (26–55) years old, were entered into the study. Their blood pressure values were more than 95/140 mm Hg (seated posture). Control group consists of thirty healthy males with normal blood pressure and their age range is 22-46 years old. Serum calcium and serum albumin were measured calorimetrically using ready for use kits. Results showed a significant decrease (p<0.05) in serum calcium of patients group as compared with control group. No significant differences noticed between the two groups in serum albumin (p>0.05). Correlation coefficients between serum albumin and calcium in control group and patients group are 0.13, and 0.12, respectively. The ratio between mean serum albumin on mean serum calcium showed an increase in patients group (23.387) in comparing with control group (19.348). In this research we conclude that hypertensive patients have significantly lower serum total calcium than control group. Calcium supplements may be required as adjuvant treatment in addition to decrease NaCl in the diet to reduce excretion of calcium in urine. There is no significant difference between the two groups in serum albumin. In this work a new ratio (S. albumin/ S. calcium) is introduced as a useful marker for calcium state. No correlation was found between serum albumin and calcium in both groups indicating the need for estimating the free calcium in both groups. Further studies required for other biochemical parameters in larger patients sample size.